Relationship between Spirituality and Emotional Maturity with Cultural Intelligence in Preventing Culture Shock - Triantoro Safaria; Khoiruddin Bashori (Psympathic : Jurnal Ilmiah Psikologi, 2022)
The role of spirituality and emotional maturity (EM) in cultural intelligence (CQ) is mostly carried out in the Westen country compared to Indonesia. Therefore, this quantitative study aims to examine the relationship between spirituality and emotional maturity (EM) with cultural intelligence (CQ). A total of 97 Psychology students from a private university in Yogyakarta were selected using purposive sampling. Data were collected using a modified scale of spirituality, emotional maturity, and cultural intelligence. The hypothesis was examined by using regression analysis. The result of the study showed a significant relationship between spirituality and cultural intelligence. Meanwhile, emotional maturity is insignificantly related to cultural intelligence.